Structural Variety in Transition Metal Complexes of Tripodal Ligands Containing Mixed Quinolyl and Pyridyl Donors - Bronte Carr; Timothy D. Christopher; Tilo Söhnel; Lawrence R. Gahan; Cassandra L. Fleming; Allan G. Blackman (ChemistryOpen)
Abstract The syntheses of the tripodal tetraamine ligands 2‐(pyridin‐2‐yl)‐N,N‐bis(quinolin‐2‐ylmethyl)ethan‐1‐amine (DQPEA), N‐(pyridin‐2‐ylmethyl)‐2‐(quinolin‐2‐yl)‐N‐(2‐(quinolin‐2‐yl)ethyl)ethan‐1‐amine (DQEPMA), 2‐(pyridin‐2‐yl)‐N,N‐bis(2‐(quinolin‐2‐yl)ethyl)ethan‐1‐amine (DQEPEA), N,N‐bis(pyridin‐2‐ylmethyl)‐2‐(quinolin‐2‐yl)ethan‐1‐amine (QEDPMA), and 2‐(pyridin‐2‐yl)‐N‐(2‐(pyridin‐2‐yl)ethyl)‐N‐(2‐(quinolin‐2‐yl)ethyl)ethan‐1‐amine (QEDPEA) containing mixed quinolyl and pyridyl moieties are reported, with 2‐vinylquinoline being used to attach quinolylethyl arms to the aliphatic N atom. X‐ray crystal structures of [(Mn(DQPEA))2O2](ClO4)2 ⋅ (CH3CN)2, [Cu(DQPEA)NCCH3](ClO4)2, [Zn(DQPEA)NCCH3](ClO4)2, [Pd(DQEPEA)Cl]Cl ⋅ 11H2O are detailed, with four, five, and six‐coordination observed. In addition, the dimeric complex [(DPEA)Co(μ‐OH)3Co(DPEA)](ClO4)3 ⋅ 0.5H2O ⋅ MeCN containing the tridentate DPEA ligand formed by N‐dealkylation of QEDPEA is reported. Calculations suggest that the very short Co…Co distance of 2.5946(6) Å in this complex is unlikely to be due to a Co−Co bond.